Geochemistry of selenium, barium, and iodine in representative soils of the Brazilian Amazon rainforest - da Silva Junior, Ediu Carlos; de Oliveira Wadt, Lúcia Helena; da Silva, Kátia Emídio; de Lima, Roberval Monteiro Bezerra; Batista, Karine Dias; Guedes, Marcelino Carneiro; de Oliveira Junior, Raimundo Cosme; dos Reis, André Rodrigues [UNESP]; Lopes, Guilherme; Broadley, Martin R.; Young, Scott D.; Guilherme, Luiz Roberto Guimarães (Elsevier, 2022)
The Amazon rainforest is a heterogeneous ecosystem and its soils exhibit geographically variable concentrations of trace elements. In this region, anthropic activities - e.g., agriculture and mining - are numerous and varied, and even natural areas are at risk of contamination by trace elements, either of geogenic or anthropogenic origin. A reliable dataset of benchmark values for selenium (Se), barium (Ba), and iodine (I) concentrations in soils is needed for use as a reference in research and public policies in the region. In this study, 9 selected sites in the Brazilian Amazon rainforest within areas represented by Oxisols and Ultisols were assessed for relevant soil physicochemical characteristics, along with the concentrations of total Se (SeTot), total Ba (BaTot), and sequentially-extracted soluble Se (SeSol) and adsorbed Se (SeAd) in 3 different soil layers (0–20, 20–40, and 40–60 cm). In addition, organically bound-Se (SeOrg) and total I (ITot) concentrations in the surface layer (0–20 cm) were measured. Soil Se concentrations (SeTot) were considered safe and are likely a result of contributions of sedimentary deposits from the Andes. Available Se (SeSol + SeAd) accounted for 4.5% of SeTot, on average, while SeOrg in the topsoil accounted for more than 50% of SeTot. Barium in the western Amazon (state of Acre) and central Amazon (Anori, state of Amazonas) exceeded national prevention levels (PVs). Furthermore, the average ITot in the studied topsoils (5.4 mg kg−1) surpassed the worldwide mean. Notwithstanding, the close relationship found between the total content of the elements (Se, Ba, and I) and soil texture (clay, silt, and sand) suggests their geogenic source. Finally, our data regarding SeTot, BaTot, and ITot can be used to derive regional quality reference values for Amazon soils and also for updating prevention (PV) and investigation (IV) values established for selected elements by the Brazilian legislation.
Keywords: Amazon soils; Availability; Geogenic; Quality reference values; Total concentration; Trace elements